2022
DOI: 10.3389/fpsyg.2022.942474
|View full text |Cite
|
Sign up to set email alerts
|

Community support and promoting cognitive function for the elderly

Abstract: Proper cognitive functions are critical to the life of the elderly. With the rapid aging of the population, community support plays an important role in cognitive functioning. This study examines the association between community support and the level of cognitive functioning in the elderly, and the mediating effect of social participation in the relationship. Based on the panel data of China Longitudinal Healthy Longevity Survey (CLHLS) in 2005, 2008, 2011, 2014, and 2018, people aged 65 and over are selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
4
1
Order By: Relevance
“…By contrast, we found no association between the lack of connective connectedness and cognitive function. Our finding was inconsistent with results from prior studies among older adults living in the community which observed a positive association of connective connectedness (such as community support) with cognitive function [ 52 ]. This difference might be explained by the different living settings of older adults.…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, we found no association between the lack of connective connectedness and cognitive function. Our finding was inconsistent with results from prior studies among older adults living in the community which observed a positive association of connective connectedness (such as community support) with cognitive function [ 52 ]. This difference might be explained by the different living settings of older adults.…”
Section: Discussioncontrasting
confidence: 99%
“…After receiving external information, the brain reaction is relatively slow, and the old people will suffer from memory loss and deterioration of thinking ability. [10] Compared with young and middle-aged people, there is a big gap in physiology and psychology of the elderly. Only by fully grasping the old people's own conditions, can the product function be further adapted to the demand of users, and the products suitable for the old people can be designed.…”
Section: Thinkingmentioning
confidence: 99%
“…The research scholars also attempt to analyze the regulation mechanism of neighborhood in uence on human health. For instance, neighborhood social participation presents a critical mechanism of neighborhood in uence on health (19,20). Meanwhile, the mediating effect of neighborhood social interaction exhibits an in uence on the neighborhood's economic status and mental health (21).…”
Section: Literature Reviewmentioning
confidence: 99%